Conservation values of understory vascular plants in even- and uneven-aged Nothofagus antarctica forests - Martínez Pastur, Guillermo José; Rosas, Yamina Micaela; Cellini, Juan Manuel; Barrera, Marcelo Daniel; Toro Manríquez, Mónica del Rosario; Huertas Herrera, Alejandro; Favoretti Bondar, Santiago; Lencinas, María Vanessa; Peri, Pablo Luis (Biodiversity and Conservation)
Usually, stands with aging trees are considered forests with higher conservation values, regardless their structural diversity and other functional attributes. Natural stands present a wide range of age structures, from even-aged stands growing at different development growth phases (e.g. CO = stands at initial or final optimum development growth phase, MD = stands at mature or decaying development growth phases) to uneven-aged stands with mixed development growth phases (e.g. UOG = stands combining mature or decaying development growth phases with initial or final optimum development growth phases, UMD = stands combining only mature and decaying development growth phases). The aim of this work was to compare richness and cover of understory vascular plants of even- and uneven-aged stands of Nothofagus antarctica (ñire) forests in Tierra del Fuego (Argentina), and relate these characteristics with abiotic, soil and forest structure variables. A total of 75 stands were sampled across the natural range distribution of the forests, where understory (point intercept method), forest structure (angle count sampling and eye-fish photos) and environmental (soil) variables were measured. 17 one-way ANOVAs were conducted using Tukey test at p < 0.05 to compare the means. Among forest structure and environmental variables, cover (F = 4.3, p = 0.007), radiation (F = 4.4, p = 0.006), phosphorous (F = 3.9, p = 0.012), tree density (F = 10.3, p < 0.001), tree diameter (F = 10.3, p < 0.001) and stand growth (F = 4.9, p = 0.004) showed significant differences, and in general with a positive or negative trend across the MD—UMD—UOG—CO gradient. Total (F = 6.5, p < 0.001) and native species richness of the understory (F = 7.2, p < 0.001) were significantly different among forest types, where UMD > UOG > MD > CO (17–28 total, and 13–24 native species, respectively). Neither exotic species richness (4–5 species) nor understory cover significantly changed among treatments (total, dicots, ferns and bryophytes). ...